Предмет: Алгебра,
автор: sergushinadasha
-- 697. Решите уравнение: а) (3х - 1)(5х + 4) - 15х2= 17; 6) (1 - 2x)(1 - 3x) = (6x - 1)x - 1; В) 12 - х(х – 3) = (6 - x)(х + 2); с (х + 4)(х + 1) = х - (х – 2)(2 - x). - -
Ответы
Автор ответа:
0
Ответ:
а) 3
б) 0,5
в)0
г)0
Объяснение:
а)
б)
в)
г)
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: qewqsadd
Предмет: Русский язык,
автор: fitnestrener
Предмет: Русский язык,
автор: vanarodionov5680
Предмет: Литература,
автор: Аноним